Effect of Ozonated Water Treatment on Fatty Acid Composition and Some Quality Parameters of Olive Oil. (4th March 2017) - Kırış, Sevilay; Velioglu, Yakup Sedat; Tekin, Aziz
ABSTRACT: The organic olives from Çine-Aydın (Turkey) were washed with tap or ozonated water for 2 and 5 min, respectively, and pressed to olive oil. The effects of wash treatments on fatty acid composition and several quality parameters of the oils were determined. The maximum values after 2-min ozonated water washes were 9.58 meqO2 /kg, 0.73%, 2.44 and 0.16 for peroxide, free acid, K232 and K270 values, respectively, which were under the standard limits for extra-virgin olive oil. Five min of ozonated water washes also yielded acceptable results, except for a slight excess on K232 value. Ozonated water washes had almost no effect on fatty acid composition.